2022
DOI: 10.5194/amt-15-3075-2022
|View full text |Cite
|
Sign up to set email alerts
|

Boundary-layer height and surface stability at Hyytiälä, Finland, in ERA5 and observations

Abstract: Abstract. We investigate the boundary-layer (BL) height at Hyytiälä in southern Finland diagnosed from radiosonde observations, a microwave radiometer (MWR) and ERA5 reanalysis. Four different, pre-existing algorithms are used to diagnose the BL height from the radiosondes. The diagnosed BL height is sensitive to the method used. The level of agreement, and the sign of systematic bias between the four different methods, depends on the surface-layer stability. For very unstable situations, the median BL height … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…total number of particles up to 150 nanometers and clwc, occurred below about 1000 meters a.s.l. which is roughly the estimated average PBL height during summer period at SMEAR-II (Sinclair et al, 2022), with larger increases, in both particles number and clwc, slight below the 1000 m a.s.l altitude. Climatic feedbacks from biogenic particles over boreal area were very recently reported in Yli-Juuti et al, 2021 by the means of remote sensing and ACSM observations available at the SMEAR-II stations.…”
Section: Sensitivity Of Bsoa Formation To C5h8 Emissionssupporting
confidence: 64%
“…total number of particles up to 150 nanometers and clwc, occurred below about 1000 meters a.s.l. which is roughly the estimated average PBL height during summer period at SMEAR-II (Sinclair et al, 2022), with larger increases, in both particles number and clwc, slight below the 1000 m a.s.l altitude. Climatic feedbacks from biogenic particles over boreal area were very recently reported in Yli-Juuti et al, 2021 by the means of remote sensing and ACSM observations available at the SMEAR-II stations.…”
Section: Sensitivity Of Bsoa Formation To C5h8 Emissionssupporting
confidence: 64%
“…The boundary layer (BL) is the lowest part of troposphere and connects the ground and the free atmosphere. The average boundary layer height at Hyytiälä SMEAR II Station in autumn (October) was around 500 m (Sinclair et al, 2022), explaining why we found higher BC concentration at high altitudes. For comparison, Table 2 shows the BC mass concentrations measured at high altitudes in different areas.…”
Section: 6comparison Of Nitrogen-containing Compounds and Other Vocs ...mentioning
confidence: 65%
“…The Heffter method often overestimates MBLH, and the definition of thresholds was found challenging (see discussion in Caicedo et al, 2020, and references therein). Sinclair et al (2022) find that agreement and sign of systematic biases depend on atmospheric stability. The T b regression method (Cimini et al, 2013) provides height estimates that are mostly consistent with the bulk Richardson approach.…”
Section: Capabilities and Limitationsmentioning
confidence: 80%